PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2016-2018 - Fajar Maulana Nur Amin; Afifudin Afifudin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to determine the effect of the Capital Structure and Company Size on Company Values in Manufacturing companies listed on the Stock Exchange for the period 2016-2018. There are 30 Manufacturing companies that are taken using Purposive Sampling techniques, namely the selection of samples based on certain criteria. The data collection method used is the documentation method of collecting and recording secondary data in the form of 2016-2018 financial statements for manufacturing companies listed on the Indonesia Stock Exchange. The data analysis technique used in this study is the data normality test, multiple linear regression, classical assumption test. The results of the study prove that simultaneously the capital structure variables and firm size have a significant effect on the value of manufacturing companies on the IDX. Partially the capital structure has a positive and significant effect on firm value and firm size has a positive and significant effect on the value of manufacturing companies on the IDX. The results of this study can be used as a consideration for investors in deciding to invest.Keywords: Capital Structure, Company Size, and Company Value.